ANALISIS DAMPAK COVID-19 TERHADAP PENDAPATAN USAHA MIKRO KECIL MENENGAH (UMKM) (Studi Pada Industri Tahu di Kelurahan Brang Biji) - U Usman; A Asmini; Budi Sastra (Jurnal Ekonomi & Bisnis, 2021)
The purpose of this study was to know the difference income of Micro, Small and Medium Enterprises (UMKM) of tofu industry in Brang Biji Village before and during the COVID-19 pandemic.The type of this study was comparative with quantitative methods.The technique used to collect data in this study were interviews and documentation. Technique used to analyze data was used paired samples T-Test with SPSS version 16.00. Based on data analysis it was known that there were differences income of UMKM tofu industry in Brang Biji Village before and during the Covid-19 pandemic.The total income of tofu traders in Brang Biji Village were decreased during the Covid-19 pandemic, where the average income of tofu industry was of Rp 2,107,700, if compared to the year before Covid-19, the average income of tofu industry was Rp 2,653,800.The government's policy during covid-19 namely physical and social distancing and large-scale social restrictions (PSBB) had an impact toward reducing sales activity because all work were done from home (work from home) so that the income received by tofu businesses were decreases.In addition, the reducing of income was also caused the low communities purchasing power.